2020
DOI: 10.1200/jco.2020.38.6_suppl.613
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab (NIVO) in combination with stereotactic body radiotherapy (SBRT) in pretreated patients (pts) with metastatic renal cell carcinoma (mRCC): First results of phase II NIVES study.

Abstract: 613 Background: NIVO showed an increased on OS in pre-treated mRCC. The introduction of metastasis SBRT could improve the clinical outcomes. NIVES Study evaluated the efficacy and safety of SBRT in combination with NIVO in II and III line of mRCC pts. Methods: This is a phase II, single arm, multicentre study in mRCC pts with PD after ≤2 prior anti-angiogenic therapies with measurable metastatic sites, and at least one suitable for SBRT. The pts received hypofractionated radiation in 1 lesion at dose of 10 Gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Progression-free survival was 4.1 months, median OS was 22.07 months, and 1-year PFS and OS rates were 32.6 and 73.4%, respectively. Grade 3-4 toxicities were observed in 24.6% of patients and none of these occurred within the radiation field (31). RADVAX RCC evaluated the combination of nivolumab and ipilimumab with SBRT, with most patients having previously undergone nephrectomy (68%).…”
Section: Discussionmentioning
confidence: 99%
“…Progression-free survival was 4.1 months, median OS was 22.07 months, and 1-year PFS and OS rates were 32.6 and 73.4%, respectively. Grade 3-4 toxicities were observed in 24.6% of patients and none of these occurred within the radiation field (31). RADVAX RCC evaluated the combination of nivolumab and ipilimumab with SBRT, with most patients having previously undergone nephrectomy (68%).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic therapy with vascular endothelial growth factor tyrosine kinase inhibitor (VEGF-TKI) should be considered to achieve tumor size reduction and then attempt local therapy to render complete remission. The recent results of combinations of stereotactic body radiation therapy (SBRT) and immune checkpoint-based systemic therapy studies have demonstrated response rates and overall outcomes no different than those with systemic therapy alone ( 8 , 9 ). However, if adrenal lesions are present as a sanctuary site after immune therapy, then use of local therapy is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…The NIVES study, a phase II multicenter trial evaluated the combination of nivolumab (240 mg every 2 weeks) with SBRT (10 Gy × 3 fractions 7 days after the first infusion of nivolumab) in advanced RCC that progressed on up to two prior systemic therapies [41]. The primary endpoint was not reached with an objective response rate of 17.4% (for an expected rate of 40%).…”
Section: Head and Neckmentioning
confidence: 99%